FINANCIAL LITERACY OF FIRST-SEMESTER UNIVERSITY STUDENTS: INSIGHTS FROM PISA FINANCIAL TASKS IN INDONESIA - Aminah Ramalia; Duano Sapta Nusantara; Amirul Mukminin; Florante Ibarra (Brillo Journal, 2026)
This study examines the financial literacy competencies of first-semester university students, focusing on their ability to interpret authentic financial documents such as pay slips and bank statements. Using the PISA financial literacy framework, the study employed a qualitative descriptive design involving 32 students from Universitas Jambi. Data were collected through open-ended tasks and semi-structured interviews, with three representative cases analyzed in depth. The findings show that most students could perform basic calculations, including identifying gross and net income, but experienced difficulties in more complex financial reasoning. Common errors involved misunderstanding recurring administrative fees and ignoring prior balances when calculating final account totals. Interviews revealed that students often relied on estimation rather than systematic reasoning, indicating a stronger procedural than conceptual understanding of financial information. The study highlights the importance of pedagogical approaches that promote interpretive and analytical reasoning beyond computation. It recommends the use of contextualized, open-ended financial tasks based on the PISA framework and encourages interdisciplinary collaboration between mathematics and economics education to strengthen students’ financial literacy and decision-making skills.